Activities and molecular characterization of petroleum hydrocarbons degrading rhizobacteria from mangrove plants (Rhizophora sp.) in Kulon Progo, Yogyakarta, Indonesia - Vivekananda Vinsensius Benget; ENDAH RETNANINGRUM (Society for Indonesian Biodiversity, 2020)
Abstract. Benget VV, Retnaningrum E. 2020. Activities and molecular characterization of petroleum hydrocarbons degrading rhizobacteria from mangrove plants (Rhizophora sp.) in Kulon Progo, Yogyakarta, Indonesia. Biodiversitas 21: 21-27. The increasing number of human population density around mangrove ecosystems has resulted in its pollution, particularly oil spills. Rhizobacteria have metabolic abilities that make them possible to live in polluted environmental conditions and the potential to be biological agents for oil remediation. However, investigations of rhizobacteria especially from rhizospheres of mangrove plants (Rhizophora sp.) and their potential use in remediation remains limited. Therefore, the purposes of this research were to investigate the ability of selected isolate in the degradation of petroleum hydrocarbons and identify its isolate using 16S rRNA gene. Observation of that degradation ability was conducted by inoculating the isolate in Bushnell-Haas Minimal Salt (BHMS) medium containing crude petroleum 0.01 %. After 10 days of incubation, the degradation hydrocarbons were analyzed by measuring Total Petroleum Hydrocarbons (TPH) using Gas Chromatography-Flame Ionization Detector (GC-FID) method. Four rhizobacteria isolate from rhizospheres of mangrove plants (Rhizophora sp), NMKP1, NMKP2, NMKP3, and NMKP4 were analyzed based on their growth in Bushnell-Haas Minimal Salt (BHMS) medium containing crude petroleum 0.01 %. The results revealed that NMKP4 isolate had the highest specific growth rate. In addition, it could degrade those hydrocarbons pollutants as much of 98.72 % within 10 days. Based on molecular characterization showed that NMKP4 isolate was in the same cluster as Pseudomonas sp. CO03.